Pengaruh Profitabilitas dan Ukuran Perusahaanterhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2018-2021 - Siti Hajar; Taufiq Risal (Jurnal Manajemen Riset Inovasi, 2023)
Firm value is an investor’s perception of the manager’s level of success in managing the company’s resources entrusted to him which is often associated with stock prices. This study aims to examine and analyze the effect of profitability and firm size on firm value in pharmaceutical companies listed on the Indonesia Stock Exchange. The type of research used in this research is quantitative research with a descriptive approach. The population and samples used in this study amounted to 12 which were taken using purposive sampling method. The results of this study prove that profitability has a positive and significant effect on firm value in pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2018-2021. And company size has a positive and significant effect on company value in pharmaceutical companies listed on the Indonesia Stock Exchange for the 2018-2021 period. Profitability and company size have positive and significant effect on company value in pharmaceutical companies listed on the Indonesia Stock Exchange for the 2018-2021 period.